FEATURES OF FISCAL ADJUSTING OF LARGE TAXPAYERS - Medynska , T.V.; Malets , A.T. (The actual problems of regional economy development, 2016)
The article is sanctified to the actual subjects is research of problems of the fiscal adjusting from the side of the state, and in particular, study of features of the fiscal adjusting of large taxpayers (ВПП) in Ukraine, his generalization and systematization, determination of priority directions of his perfection. Results are represented in the analysis of fiscal environment of doing business in Ukraine, нармативно-правового legislation in relation to the features of registering and administration of ВПП. A novelty consists in the поглибленному study of теоретико-методологічних principles in the field of the fiscal adjusting of ВПП. Practical meaningfulness is taken to the grant of concrete suggestions on the way of perfection of these processes. JEL: H 32